Peranan Klausul Standar Baku dalam Perjanjian Kredit Bank - Author: Suyitno; budi agus riswandi (Fakultas Hukum Universitas Islam Indonesia, 2000)
The form of a standard contract is much applied in the practice of a bank credit agreement. It is aimed at ensuring loan credited by a debtor. Thus, this loan is essentially fund belonging to customers. Consequently, a bank, on the one hand, is obliged to pay attention to the debtor's vested interest. As a result, the aspect of a balance in an agreement is met if the debtor's vested interestis included in the agreement.